ETNISITAS, KREATIFITAS, DAN IDENTITAS DALAM WACANA SENI BUDAYA BANGSA - Suherni - (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2013)
Identity is a political tool that is used to develop pride and love of one’s own culture, and it requires creativity in the treatmentof the ethnicity of our own art and culture. Local governments play an active role in creating conditions for the growth anddevelopment of art and culture which they consider to have promising prospects. The active role of the government in creativeart activities on one hand has the positive effect of producing large numbers of performing art events, but on the other hand ithas the negative effect of causing artists and or art practitioners to become dependent on such events for their artistic existence.The Indonesian society is highly complex one and this plurality is evident in the large number of ethnic communities andcultures, as well as the unique expression of their arts. This diversity is shown in the presence of the wide variety of Indonesianarts which are an invaluable source of wealth. This diversity is the result of the strong identity of each ethnic art form.Keywords: ethnicity, creativity, identity.